Repetition as an Emotional-expressive Marker of Bohdan Melnychuk’s Poetic Idiolect (Linguostylistic Studies, 2022)
This paper analyzes repetition as a syntactic expression and idiolectic marker of the language style of Bohdan Melnychuk ‒ a Ukrainian writer, publicist, doctor of philological science, and professor at Yuriy Fedkovych Chernivtsi National University. The unique linguistic world created by Bohdan Melnychuk is enriched by various linguistic forms, figurative and rhetorical constructions, stylistic means of melodiousness and aesthetics. However, the repetition is predetermined by the aesthetic intentions to create extremely high emotionality within the text, strengthen the expressiveness of the author’s discourse, and convey personal experiences and feelings. The relevance of the study is viewed in the need to analyze repetition as a marker of the author’s intention in the poetic text. It is a special stylistic device used by the writer to express a thought, to verbalize his communicative plan.The analysis of the collection of poems «On the Oleshkiv Rivers» has revealed the expressive potential of repetition, its partial linguistic affiliation and intentionality. The author substantiates the argument that by using different types (lexical, sound, syntactic) of reiterations, the writer deepens the meaning of the statement, actualizes the opinion, depicts various facets, circumstances and situations of human life, and reflects the struggle between good and evil, light and darkness; he conveys the touching moments of his life, shares memories, which dynamize and rhythmize poetic communication.Using the rich illustrative material the author characterizes figurative-rhetorical constructions based on repetition components (anaphora, epiphora, refrain, polysyndeton), which create expressiveness and melodic features of the poetic text, accentuate the addressee’s attention, verbalize aesthetic intentions. Moreover, they demonstrate the poet’s intention to emphasize a particular opinion, focus attention on it, intrigue, avoid monotony in the expression of the communicative plan, and reflect the individual-author perception of the world. The study outlines the communicative-intentional range of aphoristic statements that convey the axiological mindset of the poet, his metaphorical and figurative vision of the world, perception of certain events, facts, and images and generally testify to the versatility of Bohdan Melnychuk’s poetic idiolect.
Keywords: poetic text; syntactic expression; communicative intention; expressiveness